Effect of n-type doping level on direct band gap electroluminescence intensity for asymmetric metal/Ge/metal diodes. (30th August 2017) - Maekura, T; Tanaka, K; Motoyama, C; Yoneda, R; Yamamoto, K; Nakashima, H; Wang, D
Abstract: The direct band gap electroluminescence (EL) intensity was investigated for asymmetric metal/Ge/metal diodes fabricated on n-type Ge with doping levels in the range of 4.0 × 10 13 –3.1 × 10 18 cm −3 . Up to a doping level of 10 16 cm −3 order, commercially available (100) n-Ge substrates were used. To obtain a doping level higher than 10 17 cm −3 order, which is commercially unavailable, n + -Ge/p-Ge structures were fabricated by Sb doping on p-type (100) Ge substrates with an in-diffusion at 600 °C followed by a push-diffusion at 700 °C–850 °C. The EL intensity was increased with increasing doping level up to 1.0 × 10 18 cm −3 . After that, it was decreased with a further increase in n-type doping level. This EL intensity decrease is explained by the decreased number of holes in the active region. One reason is the difficulty in hole injection through the PtGe/n-Ge contact due to the occurring of tunneling electron current. Another reason is the loss of holes caused by both the small thickness of n + -Ge layer and the existence of n + p junction.